When internet service providers should be called to block and take down online materials?: the Malaysian approach - Daud, Mahyuddin; Abdul Ghani Azmi, Ida Madieha; Ismail, Suzi Fadhilah (Lexis Nexis, 2018)
Internet service providers ('ISP') have been seen as convenient callers to stem out online illegal and harmful materials -- just like The Ghostbusters in the case of strange sightings in the neighbourhood. Since ISPs are 'gatekeepers' of the digital world, they continue to receive requests to block access to illegal and harmful materials that allegedly breached national laws. To a significant extent, ISPs were forced to become the 'Internet police' -- which went against their main purpose of business. In order to encourage ISPs' freedom to operate, notice and takedown procedure was recognised as legal means to protect them from any third party liability for hosting such materials. This article begins with an overview of Vision 2020, which Page 1 provides the main framework for the development of Internet industry in Malaysia. Due to such vision, more companies that provide Internet access have 5 MLJ clxii at clxiii been incorporated. In order to protect ISPs' freedom to operate, Malaysia has adopted 'safe harbour' that recognised limited liability through notice and takedown procedure. However, this article reveals that the Malaysian version of notice and takedown procedure could invite supposition that censorship or Internet policing is taking place -- which goes against global trends that had moved towards private notice system